Zakat and poverty: an Indonesia experience / Rini Rini and Fatimah Fatimah - Rini, Rini; Fatimah, Fatimah (Faculty of Accountancy, 2019)
This study aims to examine the effect of zakat collection and distribution on poverty in Indonesia. The sample of this research is data on collection and distribution of zakat from 34 provinces in Indonesia obtained from BAZNAS. The method of determining the sample used is purposive sampling method. The hypothesis testing of this study was carried out by linear regression method consisting of two linear regression equation models. The results of this study indicate that zakat collection has an influence on the distribution of zakat and also the distribution of zakat has the influence on poverty alleviation. Distribution of zakat in Indonesia itself is still consumptive, while to maximize the function of zakat itself in order to be able to alleviate poverty and improve people's welfare in Indonesia is by maximizing zakat productively.